Endocrinology of Aging: A Short Review - Razina Sultana (International Journal of Medical Toxicology and Legal Medicine, 2024)
Significant progress in health and social well-being has resulted in steady increases in life expectancy, accompanied by a growing burden of age-related health issues. The complex changes in hormonal systems that govern homeostasis and survival may contribute to the challenges faced in later life, as illustrated by the increased risk of fractures in post-menopausal women. As individuals age, there are notable changes in hormone production, metabolism, and function. With advancing age there are significant alterations in hormone production, metabolism, and action. Some of these changes may play a role in the pathophysiology of senescence, although the evidence for that is limited. The magnitude of age-related alterations is highly variable and sex dependent. While only minor adjustments are observed in pituitary function, adrenal gland activity, and thyroid performance, the alterations in glucose regulation, reproductive health, and calcium metabolism are more pronounced. In light of these findings, strategies to locally regulate hormone bioavailability by altering pre-receptor metabolism may offer greater therapeutic potential in the fight against age-related disease.This review aims to provide an overview of the aging endocrine system and its probable impact on health and disease in the elderly. Here the strategies of evaluation and management protocols appropriate for the elderly with suspected endocrine dysfunction is defined. This review also confers the possible therapies against aging and new research works in delaying aging.